A Moloney Murine Leukemia Virus-Based Retrovirus with 4070A Long Terminal Repeat Sequences Induces a High Incidence of Myeloid as Well as Lymphoid Neoplasms - Wolff, Linda (American Society for Microbiology, 2003)
Retroviruses can be used to accelerate hematopoietic cancers predisposed to neoplastic disease by prior genetic manipulations such as in transgenic or knockout mice. The virus imparts a second neoplastic “hit,” providing evidence that the initial hit is transforming. In the present study, a unique retrovirus was developed that can induce a high incidence of myeloid disease and has a broad host range. This agent is a Moloney murine leukemia virus (Mo-MuLV)-based virus that has most of the U3 region of the long terminal repeat (LTR) replaced with that of retrovirus 4070A. Like Mo-MuLV, this virus, called MOL4070LTR, is NB-tropic and not restricted by Fv1 allelles. MOL4070LTR causes myeloid leukemias in ca. 50% of mice, a finding in contrast to Mo-MuLV, which induces almost exclusively lymphoid disease. The data suggest that the LTR of the 4070A virus expands the tissue tropism of the disease to the myeloid lineage. Interesting, MCF recombinant envelope was expressed in the lymphoid but not the myeloid neoplasms of BALB/c mice. This retrovirus has the potential for accelerating myeloid disease in genetically engineered mice.